Kepuasan Pasien Post Partum terhadap Kualitas Hidup di Ruang Bersalin - Abiyyu Purnanda; Hilda Maulyda Utamie; Dety Mulyanti (Jurnal Sains dan Kesehatan, 2023)
The labor period causes physiological, physical, and psychological changes in the patient that can affect the quality of life, such as vaginal delivery or caesarean section, skin contact, breastfeeding, and the psychological state after childbirth. Treatment by health facilities must include the level of safety, effectiveness, timeliness, organization, feasibility, and approach to patients from the external side that will affect the patient. Health services must be efficient; on the other hand, poor or unqualified health services will decrease the quality of life of postpartum patients. This review contains information on how postpartum patient satisfaction affects the quality of life in the delivery room.